Description of the nature of physical culture of a personality of specialist of physical training and sport - Іваній Ігор Володимирович (Ihor Ivaniу) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: prove the nature of physical culture of a personality of specialist of physical training and sport. Material and Methods: The bases for this article are materials of special literature, in which there was developed some aspects of the theory of physical culture. Results: it was shown that physical culture of a personality of specialist is a component of its general and professional culture and professional competence; it is the basis of social-professional maturity which is acquired in the process of professional training and activity. Conclusions: physical culture of a personality is a complex integrated formation in the structure of specialist’s personality, unites professional and personality aspects and also stipulates formation of physical, sport and life position of specialist of physical training and sport.